KAJIAN PENYUSUNAN DATA BASE PENATAAN KECAMATAN DI KABUPATEN BANDUNG - Widanarto, Agustinus (Departemen Ilmu Pemerintahan FISIP UNPAD, 2017)
The title of this research was A Study of the Creation of a Database for an Arrangement of Localities in Bandung District. Its background was a study of local potentials in attempt to measure and evaluate the variables or criteria of the local potentials required to know a possible arrangement of localities in Bandung District. The research results were expectedly useful as a material in determining the best choice for the Regional Development and Arrangement in Bandung District. The objective of the research was to obtain a description on the capacity of localities in implementing regional autonomy, and to know the possibility of development and arranging the whole localities in Bandung District to perform development and arrangement in kecamatan (sub district) level. The research was an application of measurement and evaluation models to the capacity of the potentials that describe and explain the strength level or effect of the observed variables on the success of governmental implementation, in order to enhance the implementation of public services, development, and democratization. By the approach, it could be found out objectively and deeply the capacity of the potensials that the sub-distric possess in implementing governance by measuring the indicators and sub-indicators of some variables, namely: demography,orbitation, health education, religious facility, sport facility, transportation, communication, public lighting, political awareness, security and social order, agriculture, fishoing, husbandry, labor, social-cultural, community economy, social community, and administrative aspects. Both primary and secondary data were obtained from 31 (thirty one) sub- districs in BandungÂ District, in form of qualitative and quantitative data. A sub- district might be split if it owns potentials at a high interval (1.008< TS<1.680). It might be split on condition that its potentials were at an interval of (644< TS< 1.008), and decided as fail or rejected to be split if a sub-district achieved a total score of less than 644. The evaluation and measurement results of the potentials of sub-district in Bandung District could be explained as follows: The scoring of village monographic secondary data on the 31 sub-districs to be split produced a result that there were 14 (fourteen) sub-districts falling into a category of being feasible to split, namely: Rancabali, Pangalengan, Pacet, Cicalengka, Nagreg, Rancaekek, Majalaya, Ciparay, Baleendah, Margaasih, Margahayu, Dayeuhkolot, Bojongsoang, and Cilaunyi.